A Community-Based Approach Promoting Household Plastic Waste Upcycling Through Craft-Making in Labis, Johor - Chandran, Yalini; Ali, Roslinda; Md Yusof , Muhammad Ezzwannuddin (Progress in Engineering Application and Technology, 2026)
The study addresses the issue of plastic waste mismanagement in Malaysia, particularly in Labis, Johor, and aims to promote practical intervention through hands-on recycling education. It has three main objectives: to assess knowledge and recycling behaviors regarding plastic waste, to evaluate the effectiveness of craft-making workshops in promoting upcycling, and to determine respondents' willingness to adopt recycling and upcycling in their daily lives. The research involved a three-phase intervention, and data analysis was conducted using SPSS and Microsoft Excel. The study found no significant difference in awareness levels based on student status; however, a notable difference was observed in willingness to engage in plastic craft production. Evaluation of the demonstration program revealed that participants primarily valued its contribution to global environmental sustainability and personal enjoyment, though limited participation and time constraints were identified as primary weaknesses. To enhance future initiatives, respondents recommended broader advertisement strategies and the implementation of follow-up programs to sustain community engagement. These results suggest that targeted community initiatives can effectively enhance participation in waste management. Future research should consider a longitudinal approach and compare rural and urban areas to understand the influence of social cohesion on the success of such initiatives.